Contrasting CO2 concentration discharge dynamics in headwater streams: A multi‐catchment comparison. Issue 2 (3rd April 2013) - Dinsmore, K. J.; Wallin, M. B.; Johnson, M. S.; Billett, M. F.; Bishop, K.; Pumpanen, J.; Ojala, A.
Abstract: [1] Aquatic CO2 concentrations are highly variable and strongly linked to discharge, but until recently, measurements have been largely restricted to low‐frequency manual sampling. Using new in situ CO2 sensors, we present concurrent, high‐frequency (<30 min resolution) CO2 concentration and discharge data collected from five catchments across Canada, UK, and Fennoscandinavia to explore concentration‐discharge dynamics; we also consider the relative importance of high flows to lateral aquatic CO2 export. The catchments encompassed a wide range of mean CO2 concentrations (0.73–3.05 mg C L −1 ) and hydrological flow regimes from flashy peatland streams to muted outflows within a Finnish lake system. In three of the catchments, CO2 concentrations displayed clear bimodal distributions indicating distinct CO2 sources. Concentration‐discharge relationships were not consistent across sites with three of the catchments displaying a negative relationship and two catchments displaying a positive relationship. When individual high flow events were considered, we found a strong correlation between both the average magnitude of the hydrological and CO2 response peaks, and the average response lag times. An analysis of lateral CO2 export showed that in three of the catchments, the top 30% of flow (i.e., flow that was exceeded only 30% of the time) had the greatest influence on total annual load. This indicates that an increase in precipitation extremes (greater high‐flow contributions) may have a greater influence on the flushing of CO2 from soils to surface waters than a long‐term increase in mean annual precipitation, assuming source limitation does not occur. Key Points: Concentration‐discharge relationships were not consistent across catchments Bimodal concentration distributions indicate distinct CO2 sources In the 3 headwater streams, top 30% of flow was most important to total export